Effect of bird-strike on sandwich composite aircraft wing leading edge - Arachchige, B.; Ghasemnejad, Hessam; Yasaee, Mehdi (Elsevier, 2020)
In this paper, a parametric numerical study is performed on the sandwich composite leading edge to analyse the effect of skin thickness, layups, impact velocities to compare the performance of the two different reinforcements within sandwich leading-edge structures. The detailed numerical analysis of a composite leading edge reinforced with honeycomb and foam is developed using explicit finite element software, LS-DYNA. Initially, the study proposes the most suitable equations of state for impact on the metallic leading edge for different bird geometries made from Lagrangian and SPH methods. All the numerical results are verified with available experimental data in the literature. The results will deliver a cost-efficient and accurate numerical model which assists aircraft designers in deciding the combination of design variables resulting in improved impact resistance for sandwich aircraft structures under soft body impacts.
Keywords: Bird strike; Lagrangian; Sandwich; Leading edge; LS-DYNASPH